Tinjauan Istihsan terhadap Bai’ Al-Wafa’ dan Implikasi Konsistensi Bermadzhab di Baitul Maal Wa Tamwil Sidogiri Cabang Bondowoso - Ubaidillah Ubaidillah; Nawawi Nawawi (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2017)
The birth of the first Syaria Bank in Indonesia is PT Bank Muamalat Indonesia (BMI). However, lately many emerging syaria-based financial institutions other, cultivated syaria cooperative in the form of BMT. While the legal basis bai 'al-wafa' according Hanafi’s madhhab is istihsan. Istihsan is the turning of a mujtahid from qiyas street jaly (real) to qiyas the khafi (vague) or the turning of a mujtahid from law kulli (general) to the law istitsna`i. The result of the research shows the bai 'al-wafa agreement in BMT Sidogiri Bondowoso Branch is in accordance with the existing syariat in syaria economic theory. because it has fulfilled the terms and conditions, there are many differences among the ulama. But it can be underlined that this contract is based on the concept of mature istihsan, so it can be applied in Islamic finance institutions and the implications of consistent following this madhab is very good because it does not come out of the line Ahlussunnah Wal jama'ah which became a pillar firm for the Islamic religion.